CREDIT MANAGEMENT AND FINANCIAL PERFORMANCE OF COOPERATIVE THRIFT AND CREDIT SOCIETIES (CTCS) IN NJIKOKA LOCAL GOVERNMENT AREA, ANAMBRA STATE (Journal of the Management Sciences, 2025)
This study focused on credit management and financial performance of cooperative thrift and credit societies (CTCS) in Njikoka Local Government Area, Anambra State. The study was carried out to; identify the nature of credit management practices in CTCS in the study area, assess the influence of credit standards (collateral) on member loan repayment of CTCS under study and to explore the extent to which debt recovery techniques have on numbers of loan application of CTCS in Njikoka Local Government Area. Descriptive survey research design was used. The population of the study consists of 120 cooperative members of CTCS. 92 members were sampled using Taro Yamene’s formula. The data used was a primary data collected through structured questionnaire. The data collected was analysed arithmetic mean and the hypothesis was tested using Z-test with the aid of Statistical Package for Social Sciences (SPSS). The findings revealed that Credit management and financial performance of cooperative thrift and credit societies are effective in Njikoka Local Government Area, Anambra and that Low credit standards (collateral) have significant influence on member loan repayment of CTCS in the study area. The researcher recommends among others that Cooperative thrift and credit societies should enhance their payment reminder process to more advance form so as to help them in their loan recovery.
Keywords: Cooperative management; CTCS; financial performance; Njikoka LGA